2016
DOI: 10.1093/gerona/glw197
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Estrogen Levels and Self-Reported Health and Mobility Limitation in Community-Dwelling Men of the Framingham Heart Study

Abstract: Background: Self-rated health is a commonly used global indicator of health status. Few studies have examined the association of self-rated health and mobility with estrone and estradiol in men. Accordingly, we determined the cross-sectional, incident, and mediating relations between circulating estrone and estradiol levels with self-rated health, mobility limitation, and physical performance in community-dwelling men. Methods:The cross-sectional sample included 1,148 men, who attended Framingham Offspring Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Primates exposed to acute and chronic social stresses have been found to alter the reproductive axis and give rise to suppression of the secretion of reproductive hormones, leading to lower semen quality . As mentioned previously, epidemiological studies have found associations between SRH and altered circulating reproductive hormones …”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Primates exposed to acute and chronic social stresses have been found to alter the reproductive axis and give rise to suppression of the secretion of reproductive hormones, leading to lower semen quality . As mentioned previously, epidemiological studies have found associations between SRH and altered circulating reproductive hormones …”
Section: Discussionmentioning
confidence: 81%
“…The cross-sectional data showed that poorer SRH was associated with lower levels of serum testosterone, estrone, and calculated free testosterone, but longitudinal data only indicated a positive association between SRH and estrone . On the contrary, poor SRH was observed to be associated with higher serum estradiol levels in community-dwelling men aged 30 to 89 years from the Framingham Heart Study . A cross-sectional study of 466 elderly men in Finland reported null associations between SRH and sex hormones such as estradiol, testosterone, follicle-stimulating hormone, and luteinizing hormone after adjusting for age and BMI, but a positive association was observed with testosterone and free testosterone after adjusting for age.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations